Developing Urban Infrastructure: Strategic Integration of Solar-Heated Pavement Systems for Enhanced Resilience and Sustainability - Saavedra-Flores, E; Avudaiappan-, S (Elsevier B.V., 2025)
This research examines the integration and optimization of solar-heated pavement systems in urban environments, emphasizing their potential to enhance urban resilience and sustainability. Utilizing advanced materials and smart technologies, these pavements maintain safe, ice-free surfaces during winter, reducing reliance on traditional snow removal methods and their environmental impacts. The methodology focuses on a combination of experimental setups and computational simulations to analyze the design features, material advancements, and strategic integration of these systems. Quantitative findings from case studies across diverse climates demonstrate a significant reduction in energy consumption by up to 40 % and maintenance costs by 60 %, highlighting the economic and environmental benefits. The manuscript advocates broader implementation and recommends further research to optimize system efficiency and applicability in urban planning initiatives. © 2025